Centrioles and Not-Coding DNA During the Emergence and Evolution of Bilaterally Symmetric Complex Organs: Computational Models - Regolini, Marco Franco Giulio (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
The origin of complex biological symmetric structures has long been a subject of interest and debate. How new sophisticated structures arise, perfectly meshed together, and added to preexisting organs without breaking their anatomy and physiology remains challenging. A mystery is how endless amounts of new bilaterally symmetric organs (eyes, ears, limbs, kidneys) have arisen in an infinite number of species: bilateral symmetry requires two different processes (genetic pathways) for arranging and driving cells in symmetric locations in left and right structures. It is unsustainable that two different genetic codes, independent of each other and assembled by chance, have simultaneously arisen for every organ in millions of different species. Many findings have evidenced that DNA tandem repeats and centrioles are involved in morphogenesis, suggesting they have played a role in the evolution of shapes. In the absence of experimental data (given the structure of an experiment, it may not be possible to perform it: computational models allow to simulate experiments in complex systems), this paper introduces computational simulations to test and ascertain whether DNA tandem repeats, centrioles, and centrosomes can manage and accelerate the evolution of complex organs and bilaterally symmetric structures: this study focuses on the origin of new DNA sequences that, in turn, cause the evolution of genetic codes, and, ultimately, the emergence of new shapes. The present paper follows an interdisciplinary perspective that combines biology and computational modeling to understand cellular behavior across species, underlying the similarity between programming and cellular procedures. From several points of view, cellular developmental processes and computational linear algorithms seem to share the same Boolean logic algebra. The integration of programming codes, tandem repeats, centrioles, and centrosomes provides a potential framework for investigating fundamental morphogenetic processes. In conclusion, this study is a pioneering attempt to ascertain, in the evolution of complex organs, the possible role of TRs in counting cell divisions and the centriole/centrosome’s role in translating genetic codes into correct 3D spatially planned directions.